Chest wall reconstruction for sarcoma with vertical expandable prosthetic titanium ribs. First reported use in an adult patient - Kostopanagiotou, Konstantinos; A. Steimer, Desiree; E. Wojtyś, Małgorzata; O. Wee, Jon (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2021)
Resections of chest wall malignancies – primary or metastatic – require extensive experience in reconstruction techniques and often the use of prosthetic materials. Significant osseomuscular defects of the hemithorax may require reconstruction with a combination of prostheses. Targets are: a) clear resection margins and b) restoration of normal thoracic shape and functioning. The variety of prostheses is not excessive in hospitals, so novel materials may be utilized to achieve acceptable results. In order to reconstruct a large defect, we used the vertical expandable prosthetic titanium rib system (trade name: VEPTR II by Depuy Synthes Companies J&J). It has never been used before in adult patients as it is designed for correction of chest deformities in children and adolescents [1]. Hereinafter we describe our experience with VEPTR.